Pre-transplant Sarcopenic Obesity Worsens the Survival After Liver Transplantation: A Meta-Analysis and a Systematic Review - Hegyi, Péter Jenö; Soós, Alexandra; Hegyi, Péter; Szakács, Zsolt; Hanák, Lilla; Váncsa, Szilárd; Ocskay, Klementina; Pétervári, Erika; Balaskó, Márta; Eröss, Bálint; Pár, Gabriella (Frontiers in Medicine, 2020)
Background: Rising prevalence of cirrhotic cases related to non-alcoholic steatohepatitis has led to an increased number of cirrhotic patients with the coexistence of obesity and muscle mass loss called as sarcopenic obesity (SO). In patients undergoing liver transplantation (LT), the presence of SO may worsen prognosis and increase morbidity and mortality. Objective: We aimed to evaluate the effect of the presence of pre-transplant SO on the outcomes of LT. Methods: A comprehensive search was performed in seven medical databases for studies comparing morbidity and mortality of patient with SO to patients without SO (non-SO) after LT. The primary outcome was overall mortality on short- (1 year), intermediate- (3 years), and long-term (5 years). Pooled relative risks (RRs) with 95% confidence intervals (CIs) were calculated. Heterogeneity was quantified with I2-statistics. Results: Based on the analysis of 1,515 patients from three articles, SO increased overall mortality compared to non-SO at short-, intermediate-, and long-term follow-up (RR=2.06, 95% CI: 1.28-3.33; RR=1.67, 95% CI: 1.10-2.51; and RR=2.08, 95% CI: 1.10-3.93, respectively) without significant between-study heterogeneity for short- and intermediate-term (I2=0.0% for both) and considerable heterogeneity for long-term follow-up (I2=81.1%). Conclusion: Pre-transplant SO proved to be a risk factor after LT and associated with two times higher mortality at short and long-term follow-up. Since SO worsen the prognosis of patients after LT, inclusion of body composition assessment before LT may help to plan a more individualised nutritional treatment, physiotherapy, and postoperative care and may improve morbidity and mortality.